Fluktuasi Nitrat dan Fosfat Selama Satu Periode Pasang dan Surut di Selat Lombok - I Gede Ening Sumantra; Yulianto Suteja; I Nyoman Giri Putra (Journal of Marine and Aquatic Sciences, 2020)
Nitrate (NO3-) and phosphate (PO43-) are two parameters of water quality that are important for aquatic organism. Circulation of ocean currents can distribute nitrate and phosphate from one place to another. The current pattern in the waters of the Lombok Strait at the time of the tide moves from the north to the south by bringing the mass of water from the Pacific Ocean, while the movement of the current pattern at low tide moves from south to north by bringing the mass of water from the Indian Ocean. Therefore, this study aims to determine the fluctuations of Nitrate (NO3-) and Phosphate (PO43-) in Lombok Strait during one tidal period. This research was conducted on 3 - 5 November 2017 precisely at coordinates 116?1'18 "LS; -8?34'12 "BT. Sampling is done directly in the field. Seawater samples are taken on the surface and at a depth of 10 meters for 1 x 24 hours with an interval every 2 hours using a Vertical Water Sampler. Measurement of nitrate parameter using spectrophotometric method with Spectrophotometer SNI 6989 79-2011, while phosphate parameter using spectrophotometric method with UV-Vis Spectrophotometer, refer to SNI 06-6989 31-2005. The concentration of nitrate and phosphate at each time in the analysis and seen fluctuations. The concentration of nitrate and phosphate in Lombok Strait fluctuated during one tidal period. At high tide conditions, the concentrations of nitrate and phosphate are low and at low tide conditions high nitrate and phosphate concentrations.